2010
DOI: 10.1002/j.2162-6057.2010.tb01333.x
|View full text |Cite
|
Sign up to set email alerts
|

Redefining Creativity — Analyzing Definitions, Collocations, and Consequences

Abstract: How holistically is human creativity defined, investigated, and understood? Until recently, most scientific research on creativity has focused on its positive side. However, creativity might not only be a desirable resource but also be a potential threat. In order to redefine creativity we need to analyze and understand definitions, collocations, and consequences of creativity. In this paper, we reviewed 42 explicit definitions and 120 collocations. The thematic analysis of our data reveals that the vast major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0
23

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(102 citation statements)
references
References 39 publications
0
79
0
23
Order By: Relevance
“…Etymologically, creativity derives from the Latin participle "creare" which means "to make, produce", and it is also related to "crescere" which means "arise" or "grow" (Kampylis & Valtanen, 2010). According to Weiner (2000) (as cited in Sawyer, 2012, p. 19), the word "creativity" appeared for the first time in an 1875 text by Adolfus William Ward and was used to suggest that there is something similar across all disciplines.…”
Section: Defining Creativity and Innovationmentioning
confidence: 99%
“…Etymologically, creativity derives from the Latin participle "creare" which means "to make, produce", and it is also related to "crescere" which means "arise" or "grow" (Kampylis & Valtanen, 2010). According to Weiner (2000) (as cited in Sawyer, 2012, p. 19), the word "creativity" appeared for the first time in an 1875 text by Adolfus William Ward and was used to suggest that there is something similar across all disciplines.…”
Section: Defining Creativity and Innovationmentioning
confidence: 99%
“…They concluded that since each of metrics measures something different, summing up the metrics to create an overall ideation effectiveness measure makes no sense. Kampylis and Valtanen (2010) suggest that creative product(s) must be novel (original, unconventional) and appropriate (valuable, useful). In a study by Bourgeois-Bougrine et al (2017), creativity involves the production of original, potentially workable, ideas to solve a problem.…”
Section: Methodsmentioning
confidence: 99%
“…Open-ended technological and learning environments that treat microworld as "boundary objects" and allow learners to use them in personally meaningful ways, to collaboratively work with and discuss over them and their key concepts, or to question them and want to modify and improve them, are important coordinates of a context fostering various forms of creativity. We therefore argue that the seeds already exist in the theory of constructionism to address and study creativity through a more integrated conception, which is as a function of a person's ability, presuming an intentional process, occurring within a specific learning environment and entailing the generation of new products (Kampylis & Valtanen, 2010).…”
Section: Dealing Creatively With the "Difficult" Concept Of Sustainabmentioning
confidence: 98%
“…The analytical framework we employed to identify and discuss creativity is an adaptation of the categorical scheme suggested by Kampylis and Valtanen (2010). It views creativity 1) as being a function of the individual's and group's ability; 2) as being situated at the nexus of several interconnected processes; 3) as emerging from a facilitative learning context; and 4) as entailing the generation of new/novel abstract ideas and concrete outputs (digital artifacts).…”
Section: Data Collection and Analysismentioning
confidence: 99%